Kontribusi Motivasi Berprestasi dan Kreativitas Belajar Terhadap Hasil Belajar Meperbaiki Sistem Suspensi pada Siswa Program Keahliaan Teknik Kendaraan Ringan SMK Bhara Trikora II Paguyangan Brebes Tahun Ajaran 2014/2015 - Dede Imam Alimudin; Suparmin Suparmin (Jurnal Taman Vokasi, 2014)
The purpose of this study was to determine; (1) the contribution of achievement motivation and creativity of learning on learning outcomes meperbaiki suspension system; (2) the contribution of achievement motivation on learning outcomes meperbaiki suspension system; (3) the contribution of creativity to learn the learning outcomes meperbaiki suspension system on students majoring in engineering light vehicle Vocational School Bhara TRIKORA II Paguyangan Bradford School Year 2014/2015. The research hypothesis; (1) There is a positive and significant contribution between achievement motivation and creativity of learning to improve the learning outcomes of the suspension system; (2) There is a positive and significant contribution to the achievement motivation on learning outcomes improve the suspension system; (3) There is a positive and significant contribution to the creativity of learning to improve the learning outcomes of the students' suspension systems engineering light vehicle program Vocational School Bhara Trikora II Paguyangan Bradford School Year 2014/2015.         The study was conducted on May 16, 2014 till October 8, 2014 at the Vocational School Bhara Trikora II Pahuyangan Bradford. The population in this study all class XII students numbered 106 students. This study uses a sampling technique Simple Random Sampling with Harry King guideline nomogram calculations and obtained a sample of 76 students. This type of research is correlational research and categorized Ex Post Facto. Techniques of data collection by questionnaire and documentation. Test validity using product moment correlation formula. Test reliability using Cronbach alpha formula. Analysis using multiple regression analysis and partial correlation analysis. Before analysis, the data first in the prerequisite test that analyzes; normality test, linearity, and multicollinearity test.          Based on the results obtained the following results: (1) simultaneously there is a positive and significant contribution to the achievement motivation (X1) and creativity in learning (X2) to improve the learning outcomes of the suspension system (Y); (2) there is a partial positive and significant contribution to the achievement motivation (X1) to improve the learning outcomes of the suspension system (Y); (3) there is a partial positive and significant contribution to the creativity of learning to improve the learning outcomes of the suspension system (Y) on the student engineering program light vehicles Vocational School Bhara Trikora II Paguyangan Bradford School Year 2014/2015Kontribusi Motivasi Berprestasi dan Kreativitas Belajar Terhadap Hasil Belajar Meperbaiki Sistem Suspensi pada Siswa Program Keahliaan Teknik Kendaraan Ringan SMK Bhara Trikora II Paguyangan Brebes Tahun Ajaran 2014/2015